Senolytics: A Potential Fountain of Youth. - Khing S. Ong; Zack ST. Lim; Boenjamin Setiawan (Cermin Dunia Kedokteran, 2019)
Senolytics are groups of natural compounds, small molecules drugs and methods that eliminate senescent cells in the body of an organism. This review illustrate the pathogenesis or factors that lead to cellular senescence. As cellular senescence is the main culprit for age-associated diseases, the development of various classes of senolytics is of paramount importance in maintaining or even extending our health-span. Different classes of senolytics with some perspective of its potential for clinical applications will also be discussed.Senolyitcs merupakan kelompok senyawa alami, obat dan metode yang melenyapkan sel-sel tua dari tubuh. Tinjauan ini membahas patogenesis dan faktor-faktor yang menyebabkan proses penuaan sel. Mengingat penuaan sel merupakan penyebab utama penyakit-penyakit akibat penuaan, pengembangan berbagai jenis senolytics sangat penting dalam upaya mempertahankan dan memperpanjang harapan hidup. Akan dibicarakan pula beberapa kelas senolytics beserta potensi klinisnya.